Advanced Computational Methods for Knowledge Engineering Proceedings of the 4th International Conference on Computer Science, Applied Mathematics and Applications, ICCSAMA 2016, 2-3 May, 2016, Vienna, Austria - Nguyen, Thanh Binh.; van Do, Tien.; An Le Thi, Hoai.; Nguyen, Ngoc Thanh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This proceedings consists of 20 papers which have been selected and invited from the submissions to the 4th International Conference on Computer Science, Applied Mathematics and Applications (ICCSAMA 2016) held on 2-3 May, 2016 in Laxenburg, Austria. The conference is organized into 5 sessions: Advanced Optimization Methods and Their Applications, Models for ICT applications,Topics on discrete mathematics, Data Analytic Methods and Applications and Feature Extractio, respectively. All chapters in the book discuss theoretical and practical issues connected with computational methods and optimization methods for knowledge engineering. The editors hope that this volume can be useful for graduate and Ph.D. students and researchers in Applied Sciences, Computer Science and Applied Mathematics. .
Part I. Advanced Optimization Methods and Their Applications -- Part II. Models for ICT Applications -- Part III. Topics on Discrete Mathematics -- Part IV. Data Analytic Methods and Applications -- Part V. Feature Extraction.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence